Meaning construction in education: way of interpretation and algorithmic logic - Chiara Cavarra (Firenze University Press, 2020)
Positivist and interpretative paradigms, organized by different languages, methods and models, configure reality according to diametrically different logics. Today in the social sciences, of which the education is an integral part, new research methods are supported by big data detected by new technologies and sometimes provided by the same individual who is unaware of the mechanism (Saukko, 2018). While observations or interviews are interpreted through a reflective process, software that use big data stores and processes data without underlying cognitive or reflective models (Ruppert, Law, & Savage, 2013). Reasoning models (inductive, deductive and abductive), ethical and normative frameworks underlying the different paradigms will be described. Methods of qualitative research and interpretation of the fact appear particularly suitable in educational contexts in which observation directs the investigation and highlights the need for understanding (Mortari, 2007).   Costruzione del significato in ambito educativo: via interpretativa e logica algoritmica. I paradigmi positivista ed interpretativo, organizzati da linguaggi, metodi e modelli differenti, configurano la realtà secondo logiche diametralmente opposte. Oggigiorno nelle scienze sociali, di cui l'educazione è parte integrante, i nuovi metodi di ricerca sono sorretti dai big data rilevati dalle nuove tecnologie e forniti dallo stesso individuo a volte all'oscuro del meccanismo (Saukko, 2018). Mentre osservazioni o interviste vengono interpretate attraverso un processo meditativo, i software che usano i big data immagazzinano e processano i dati senza modelli cognitivi o riflessivi alla base (Ruppert, Law, & Savage, 2013). Saranno descritti modelli di ragionamento (induttivo, deduttivo ed abduttivo), cornici etiche e normative alla base dei differenti paradigmi. Metodi di ricerca qualitativa e di interpretazione del fatto appaiono particolarmente indicati nei contesti educativi in cui l'osservazione dirige l'indagine ed evidenzia il bisogno di comprensione (Mortari, 2007).